A Study of Association between Cognitive Attributions, Appraisals and Depression in Children with High Functioning Autism Spectrum Disorders - Sharma, Shilpi (Journal of Psychology and Psychotherapy Research, 2015)
Children with high-functioning autism spectrum disorders (HFASD) have been shown to exhibit co-morbid symptoms of clinical depression and also exhibit a negative attribution style. Research evidence from studies carried out with children without autism has shown a significant association between negative attributions and depression, there is however limited research evidence in the case of children with autism. The current study assessed cognitive attributions using Children’s Cognitive Style Questionnaire and depression through Beck Depression inventory, in a sample of 47 children with HFASD and 45 typically developing (TD) controls. Children in the HFASD group were found to exhibit a negative attribution style characterised by higher scores for internality, globality and stability attribution dimensions; and higher scores for depressive symptomatology, compared to the TD group. Attributions were found to be significant predictors of depressive symptomatology in a regression model, for the HFASD group.